2000
DOI: 10.1677/joe.0.1670473
|View full text |Cite
|
Sign up to set email alerts
|

Capacitative calcium entry is involved in steroidogenesis in bovine adrenocortical fasciculata cells

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 15 publications
(22 reference statements)
0
5
0
Order By: Relevance
“…The main finding of the present work was that STIM1, which plays an essential role in transmitting a decrease in store Ca 2ϩ contents to the plasma membrane, was not detected in rat AM cells at the mRNA and protein levels. On the other hand, STIM1 was expressed in adrenal cortex cells, where SOC has been implicated in the production of steroid hormones (8,44). The lack of STIM1 expression strongly suggests that SOC is absent in the rat AM cells.…”
Section: Discussionmentioning
confidence: 98%
“…The main finding of the present work was that STIM1, which plays an essential role in transmitting a decrease in store Ca 2ϩ contents to the plasma membrane, was not detected in rat AM cells at the mRNA and protein levels. On the other hand, STIM1 was expressed in adrenal cortex cells, where SOC has been implicated in the production of steroid hormones (8,44). The lack of STIM1 expression strongly suggests that SOC is absent in the rat AM cells.…”
Section: Discussionmentioning
confidence: 98%
“…1–4) which could explain the toxicity in CsA‐treated rat heart (Goldberg et al, 1989). It has been reported that voltage‐dependent L‐Type Ca 2+ ‐channel are regulated by glucocorticoids (Braun et al, 1995; Ebisawa et al, 2000). In our experimental conditions, HY inhibited CsA‐induced calcium increase as well as MDA production.…”
Section: Discussionmentioning
confidence: 99%
“…The isolated cells were cultured in Ham's F-10 medium supplemented with 5% fetal calf serum, 10% newborn calf serum, 2.5% horse serum, and antibiotics on a coverslip coated with collagen (16,17). Three-day primary cultured monolayer cells were used for the experiments.…”
Section: Primary Culture Of Bafcsmentioning
confidence: 99%
“…] i was monitored as described by Ebisawa et al (17). Briefly, BAFCs on a coverslip were loaded with 5 m M fura 2 / AM in Krebs-Ringer HEPES buffer (123.4 mM NaCl, 6 mM KCl, 1.2 mM KH 2 PO 4 , 1.2 mM MgSO 4 , 1.2 mM CaCl 2 , 2 mg / ml glucose, 2 mg / ml BSA, 10 mM HEPES, pH 7.4) supplemented with 0.02% cremophor EL for 90 min at 37°C.…”
Section: +mentioning
confidence: 99%